Asupan makan, status gizi, dan kualitas hidup pasien kanker payudara di RSUP DR Sardjito Yogyakarta - Susetyowati Susetyowati; Retno Pangastuti; Sri Retna Dwidanarti; Hanifah Wulandari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2018)
Background: Breast cancer is the fifth leading cause of death due to all the type of cancer and the second leading cause of death in developing country after lung cancer. The global incidents of this disease were 43%. The cancer cells have an ability to disturb the nutrients absorbtion in the body and give an effect of decreasing nutritional status, physical performance and quality of life.Objective: To show the relationship between nutrient intake, nutritional status and quality of life, breast cancer patients with radiotherapy at RSUP Dr Sardjito Yogyakarta.Method: This study was an observational study with cross sectional design. Total subject of this study were 85 respondents. Intake of energy, protein, fat and carbohydrate were measured using 1x24 hours food recall. Nutritional status were measured using patient-generated subjective global assessment (PG-SGA) questionnaire. Then the quality of life were measured using European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) questionnaire.Results: There were significant difference in the average intake of energy (p=0.013), protein (p=0.043) and fat (p=0.016) between severe malnourished, moderate malnourished and wellnourished patients, whereas the average intake of carbohydrate was not significant (p=0.070). The lower nutrition intake, the lower nutritional status. There was also significant difference in fat intake (p=0.035) and nutritional status based on PG-SGA (p=0.002) between patients with poor and good quality of life. Patients with poor quality of life had lower nutrition intake and nutritional status.Conclusion: Nutrient intake gave an effect to nutritional status and quality of life in breast cancer patient with radiotherapy.